2021
DOI: 10.1017/s0033291721002075
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic activity, posttraumatic and nontraumatic nightmares, and PTSD after trauma exposure

Abstract: Background Nightmares are a hallmark symptom of posttraumatic stress disorder (PTSD). This strong association may reflect a shared pathophysiology in the form of altered autonomic activity and increased reactivity. Using an acoustic startle paradigm, we investigated the interrelationships of psychophysiological measures during wakefulness and PTSD diagnosis, posttraumatic nightmares, and nontraumatic nightmares. Methods A community sample of 122 trauma survivors were presented with a ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 78 publications
2
4
1
Order By: Relevance
“…Park et al (2017) reported that individuals with PTSD from combat‐related trauma exhibited decreased waking RMSSD and HF‐power compared to healthy controls, and that daytime HRV measures of PNS activity were negatively associated with hyperarousal symptoms. Further, a study by Mäder et al (2021) conducted in a sample encompassing the participants in the present study found that HR acceleration during a loud‐tone task was associated with greater self‐reported PTSD severity. In that sample, HR acceleration significantly differed between PTSD‐diagnosed participants and trauma‐exposed controls (TECs), but HRV did not (Mäder et al, 2021).…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Park et al (2017) reported that individuals with PTSD from combat‐related trauma exhibited decreased waking RMSSD and HF‐power compared to healthy controls, and that daytime HRV measures of PNS activity were negatively associated with hyperarousal symptoms. Further, a study by Mäder et al (2021) conducted in a sample encompassing the participants in the present study found that HR acceleration during a loud‐tone task was associated with greater self‐reported PTSD severity. In that sample, HR acceleration significantly differed between PTSD‐diagnosed participants and trauma‐exposed controls (TECs), but HRV did not (Mäder et al, 2021).…”
Section: Introductionsupporting
confidence: 57%
“…Further, a study by Mäder et al (2021) conducted in a sample encompassing the participants in the present study found that HR acceleration during a loud‐tone task was associated with greater self‐reported PTSD severity. In that sample, HR acceleration significantly differed between PTSD‐diagnosed participants and trauma‐exposed controls (TECs), but HRV did not (Mäder et al, 2021). In contrast, D'Souza et al (2019) did not find an association between daytime HF‐power and PTSD symptom severity.…”
Section: Introductionsupporting
confidence: 57%
“…It is possible they feel safer sleeping in the lab, and therefore experience fewer nightmares. Mäder et al (2021) conducted a study with 122 trauma survivors to investigate the interrelationships between waking psychophysiological measures and PTSD, posttraumatic nightmares and nontraumatic nightmares. They found that both those with PTSD and posttraumatic nightmares had increased heart rate reactivity after experiencing a series of loud tones, which the authors suggest might reflect reduced parasympathetic tone.…”
Section: Nightmares and Polyvagal Theory: Links Between Ans And Night...mentioning
confidence: 99%
“… Pierce et al, 2020 , Spitzer et al, 2006 , Fancourt et al, 2021 , Faul et al, 2009 , The jamovi project 2021 , Kroenke et al, 2001 , Mäder et al, 2021 , Niedzwiedz et al, 2020 …”
Section: Uncited Referencesmentioning
confidence: 99%